2018
DOI: 10.1267/ahc.18028
|View full text |Cite
|
Sign up to set email alerts
|

New Insight into the Role of Nitric Oxide Pathways in Pancreas

Abstract: Nitric oxide (NO) is generated by a family of enzymes termed NO synthases (NOS) that convert L-arginine to NO and citrulline. The role of NO as an important biological mediator and recognition of the pathophysiological significance of superoxides/NO interaction has led to an intensive research and development of therapies based on the interception of the NO signaling cascade in the pancreatitis course. However, the presence and localization of the NO-generating enzymes in various organs including pancreas are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 44 publications
0
8
1
1
Order By: Relevance
“…As a result, the cell is getting short of bioactive NO and responses daespite of upregulation of NOS and guanylyl cyclase. 33 In the present study, the brain tissue level of NO was significantly increased; however, the cGMP level was decreased in the AD group compared to the control group. This finding implies high production of iNOS-derived NO which exerted the nitrostive effect with little physiological effect mainfested by the decreased cGMP level that may be secondary to upregulation of PDEs.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…As a result, the cell is getting short of bioactive NO and responses daespite of upregulation of NOS and guanylyl cyclase. 33 In the present study, the brain tissue level of NO was significantly increased; however, the cGMP level was decreased in the AD group compared to the control group. This finding implies high production of iNOS-derived NO which exerted the nitrostive effect with little physiological effect mainfested by the decreased cGMP level that may be secondary to upregulation of PDEs.…”
Section: Discussioncontrasting
confidence: 52%
“…At this point, the NO message may be interrupted. 33 NO, in oxidative stress and inflammatory conditions, can react with superoxide radical (O2-) to produce reactive oxygen species and reactive nitrogen species. Therefore, NO can damage the cell of its origin and cause a variety of diseases including AD.…”
Section: Discussionmentioning
confidence: 99%
“…Although, NO plays essential role in several physiological processes, nonetheless, if it accumulates, it can react with superoxide anion to produce toxic nitrite anion, thereby causing tissue damage. 43 Thus, the apparent suppression of NaF-mediated increase in NO concentration by resveratrol further suggests its anti-inflammatory property.…”
Section: Discussionmentioning
confidence: 98%
“…The expression of NOS 3 was increased in response to the presence of a NO donor, and this effect was concentration-dependent suggesting that the inhibitory effects of NO donor on survival and secretory function of β cells may be partially mediated by increased levels of NOS 3 . Although the involvement of different NOS isoforms in regulation of insulin secretion is controversial, several reports have demonstrated that NOS 3 and NOS 1 are constitutively expressed in pancreatic vasculature and neurons, respectively [ 7 ]. Compared with other isoforms, NOS 3 seems to play a major role in modulation of pancreatic secretion and has been detected in rat and human pancreatic islets; hence, the present study focused on the involvement of NOS 3 in this process [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the involvement of different NOS isoforms in regulation of insulin secretion is controversial, several reports have demonstrated that NOS 3 and NOS 1 are constitutively expressed in pancreatic vasculature and neurons, respectively [7]. Compared with other isoforms, NOS 3 seems to play a major role in modulation of pancreatic secretion and has been detected in rat and human pancreatic islets; hence, the present study focused on the involvement of NOS 3 in this process [7].…”
Section: Protein Expression Of Cholinergic Receptors In the Presence mentioning
confidence: 94%